Treatment options for recurrent platinum-resistant ovarian cancer: A systematic review and Bayesian network meta-analysis based on RCTs - Li, Juan; Zou, Guorong; Wang, Wei; Yin, Chen; Yan, Haowen; Liu, Shengpeng (Frontiers in Oncology, 2023)
Background: There are a variety of treatment options for recurrent platinum-resistant ovarian cancer, and the optimal specific treatment still remains to be determined. Therefore, this Bayesian network meta-analysis was conducted to investigate the optimal treatment options for recurrent platinum-resistant ovarian cancer. Methods: Pubmed, Cochrane, Embase, and Web of Science were searched for articles published until 15 June 2022. The outcome measures for this meta-analysis were overall survival (OS), progression-free survival (PFS), and adverse events (AEs) of Grade 3-4. The Cochrane assessment tool for risk of bias was used to evaluate the risk of bias of the included original studies. The Bayesian network meta-analysis was conducted. This study was registered on PROSPERO (CRD42022347273). Results: Our systematic review included 11 RCTs involving 1871 patients and 11 treatments other than chemotherapy. The results of meta-analysis showed that the overall survival (OS) was the highest in adavosertib + gemcitabine compared with conventional chemotherapy, (HR=0.56,95%CI:0.35-0.91), followed by sorafenib + topotecan (HR=0.65, 95%CI:0.45-0.93). In addition, Adavosertib + Gemcitabine regimen had the highest PFS (HR=0.55,95%CI:0.34-0.88), followed by Bevacizumab + Gemcitabine regimen (HR=0.48,95%CI:0.38-0.60) and the immunotherapy of nivolumab was the safest (HR=0.164,95%CI:0.312-0.871) with least adverse events of Grades 3-4. Conclusions: The results of this study indicated that Adavosertib (WEE1 kinase-inhibitor) + gemcitabine regimen and Bevacizumab + Gemcitabine regimen would be significantly beneficial to patients with recurrent platinum-resistant ovarian cancer, and could be preferred for recurrent platinum-resistant ovarian cancer. The immunotherapeutic agent, Nivolumab, is of considerable safety, with a low risk for grade-III or IV adverse events. Its safety is comparable to Adavosertib + gemcitabine regimen. Pazopanib + Paclitaxel (weekly regimen), Sorafenib + Topotecan/Nivolumab could be selected if there are contraindications of the above strategies.